Complex And Simple Appendicitis: REstrictive or Liberal postoperative Antibiotic eXposure (CASA RELAX) using Desirability of Outcome Ranking (DOOR) and Response Adjusted for Duration of Antibiotic Risk (RADAR): study protocol for a randomized controlled trial. Issue 1 (16th September 2022) - Yeh, Daniel Dante; Hatton, Gabrielle E; Pedroza, Claudia; Pust, Gerd; Mantero, Alejandro; Namias, Nicholas; Kao, Lillian S
Abstract : Objectives: After appendectomy for simple or complicated appendicitis, the optimal duration of postoperative antibiotics (postop abx) is unclear and great practice variability exists. We propose to compare restrictive versus liberal postop abx using a hierarchical composite endpoint which includes patient-centered outcomes and accounts for duration of antibiotic exposure. Methods/Design: Participants with simple or complicated appendicitis undergoing appendectomy are randomly assigned to either restricted or liberal strategy. Eligible subjects declining randomization will be recruited to enroll in an observation only cohort. The primary endpoint is an ordinal scale of mutually exclusive clinical outcomes with within-category rankings determined by duration of antibiotic exposure. Subjects in both randomized and observation only cohorts will be analyzed as intention-to-treat, per-protocol, and as-treated. Exploratory Bayesian analyses will be performed. Conclusion: The complex and simple appendicitis: restrictive or liberal postoperative antibiotic exposure multicenter randomized controlled trial will enroll surgical appendectomy patients and seeks to analyze if a strategy of restricted (compared with liberal) postoperative antibiotics results in similar clinical outcomes with the benefit of reduced antibiotic exposure. Trial registration number: NCT05002829 .